TINDAK KEJAHATAN DI LAUT: SEBUAH TINJAUAN HUKUM DAN SITUASI DI BEBERAPA KAWASAN DUNIA - Dicky Rezady Munaf; Retno Windari (Jurnal Sosioteknologi, 2011)
Sea crimes have happened since long ago. For centuries some areas of the world such as Malacca Straits and the South China Sea have been the target of the sea crimes. Generally, crimes at sea are an attack on the ship or boat. The criminals take a variety of valuables. International law has provided possibilities to combat the pirates. In the Strait of Malacca, for example, Indonesian government and several associated countries in Malacca have collaborated to solve these problems. In the Gulf of Aden and Somalia Offshore, the UN and various countries have tried to handle it even though the results have not been too encouraging. Key words: Sea crimes, combat, pirates